Agronomic traits and tuber quality attributes of farmer grown cassava landraces in Nigeria - Raji, A.A.; Ladeinde, T.A.O.; Dixon, Alfred G.O. (2007)
Eleven Nigerian cassava landraces with desirable pest and disease resistance were evaluated for 18 agronomic and tuber quality traits along with two popularly grown cultivars including an improved genotype. The improved cultivar TMS 30572 gave the highest yield, but had certain undesirable quality attributes such as high cyanogenic potential (12.86 mg HCN equivalent/100g fresh tuber weight) and low mealiness (non-poundable). Conversely, the landraces had lower cyanogenic potential (1 to 5 mg HCN equivalent/100g fresh tuber weight, considered non-toxic) and high mealiness (2.0 to 2.5 scored on a scale of 0 to 3) of boiled tubers. All cultivars exhibited relatively high dry matter percentage (33.2 to 39.2%). Taste, colour, and fibre content of boiled tubers were generally sweet to bland, white to cream, and low to moderate respectively for all cultivars. Although the landraces gave less yield than the elite cultivars, they carried genes for adaptation to local conditions, and have preferred tuber quality attributes that can be introgressed into elite germplasm development.